Opportunity entrepreneurs - potential drivers of non-farm growth in rural Vietnam? - Juergen Bruenjes; Javier Revilla Diez (Philipps-University Marburg, Department of Geography, 2012)
In this paper we apply the concept of necessity and opportunity entrepreneurship to rural Vietnam. The aim is to evaluate whether opportunity entrepreneurs in rural areas in developing countries have a greater potential to stimulate endogenous non-farm growth than necessity entrepreneurs. The results show that opportunity entrepreneurs are relatively frequent. They have an agricultural background less often and are better educated and skilled. In addition, they are more successful in terms of profits, even after controlling for general business and locational characteristics. However, even rural opportunity entrepreneurs are often not oriented towards employment growth and thus have a limited capacity to generate non'farm employment for other households. It becomes clear that although the necessity/opportunity concept has so far been primarily applied to developed countries, distinguishing opportunity and necessity entrepreneurship is very suitable in a rural developing context if some contextual specifics of the rural environment are taken into account.
Keywords: L2; O18; R23; 330; Necessity entrepreneurship; opportunity entrepreneurship; developing countries; Vietnam